Influence of social distancing during the COVID-19 pandemic on physical activity in children: A scoping review of the literature - Kenji Yomoda; Shohei Kurita (Elsevier, 2021)
Background/objectives: There is an urgent concern about physical inactivity among children caused by recent restrictions for containing the spread of the novel coronavirus disease (COVID-19). This scoping review aims to identify the impact of the pandemic and related factors on children's physical activity (PA). Methods: Twenty-one studies published in 2020 that evaluated PA among children under the age of 18 were extracted from electronic databases. The survey contexts, samples, PA measurement methods, and main findings of each study were categorized and summarized. Results: The review yielded the following results: 1) the PA of children and adolescents mostly decreased; 2) the decrease in PA was more prevalent in boys and older children and adolescents; 3) the decrease in PA was less prevalent in children who live in detached houses, houses with more space, rural areas, and with more family members; and 4) parental support and consideration of location and activity types may help children maintain or increase their PA during the pandemic. Conclusion: This review shows a decline in PA among children and raises concerns about the pandemic's impact on physical and mental health. Declines in PA appear greater among children who participate in organized team sports and those with limited space and opportunity for habitual PA at home or in their neighborhood. Public support for children and families should consider these findings to prevent the negative effects of physical inactivity.